2016
DOI: 10.5944/educxx1.17515
|View full text |Cite
|
Sign up to set email alerts
|

El Impacto Del Modelo «un Ordenador Por Niño» en La Educación Primaria: Un Estudio De Caso

Abstract: daniel losada iglesias, josé miguel correa gorospe y lorea fernández olaskoaga el impacto del modelo «un ordenador por niño» en la educación primaria...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 26 publications
0
2
0
5
Order By: Relevance
“…Some teachers have pointed out that these ICT resources could possibly be more useful for students' independent work than for regular classroom teaching. As the study of [55] showed, only four in every ten teachers use computers and the Internet every day in their teaching practices, and their use of digital whiteboards and audio-visual tools is limited. [56] also confirmed students indicating that the most frequent activities conducted in the classroom with ICT were searching for information on the Internet, working with word processors, and doing activities and exercises online.…”
Section: Assessing Ict and E-learning In Face-to Face Teaching 421mentioning
confidence: 99%
“…Some teachers have pointed out that these ICT resources could possibly be more useful for students' independent work than for regular classroom teaching. As the study of [55] showed, only four in every ten teachers use computers and the Internet every day in their teaching practices, and their use of digital whiteboards and audio-visual tools is limited. [56] also confirmed students indicating that the most frequent activities conducted in the classroom with ICT were searching for information on the Internet, working with word processors, and doing activities and exercises online.…”
Section: Assessing Ict and E-learning In Face-to Face Teaching 421mentioning
confidence: 99%
“…En efecto, la accesibilidad a dispositivos tecnológicos hace también accesibles objetivos que no tenían cabida previamente en el curriculum escolar, como la colaboración en tiempo real y el diálogo intercultural entre estudiantes de diferentes países (Jover, González Martín y Fuentes, 2015), el acceso instantáneo a muy diversas fuentes de información con grandes repercusiones para la participación cívica (UNESCO, 2011) o la visualización de figuras en 3D (Saorín, De la Torre, Martín, Carbonell y Montero, 2011) y realidad aumentada (Fombona y Vázquez-Cano, 2017;Fuentes, 2017), lo que requiere al mismo tiempo ampliar las expectativas de aprendizaje de la escuela sobre los alumnos (Prensky, 2010). No obstante, aunque se observan avances hacia un uso menos instrumental de la tecnología, no parece que estos se hayan traducido aún en mejoras generalizadas en las prácticas docentes o en un incremento sustancial del rendimiento académico de los estudiantes (Losada, Correa y Fernández Olaskoaga, 2017; Sánchez-Antolín, Alba y Paredes, 2016). Es decir, no suponen todavía un avance real hacia la tercera etapa de integración tecnológica plena.…”
Section: Introductionunclassified
“…Igualmente, estos resultados podrían estar en la misma línea que las investigaciones de Losada et al (2017) en las que se expone que una de las acciones más realizadas por el profesorado dentro del aula relacionada con el uso de las TIC es la explicación de los contenidos de los temas apoyada en la PDI. Perspectivas docentes sobre uso y efectividad de recursos TIC para promocionar el aprendizaje colaborativo, la creatividad y el espíritu emprendedor ~ 77 ~ Estos recursos son de uso más general.…”
Section: Herramientas O Recursos Tic Utilizados Y Frecuencia De Usounclassified